THE ROLE OF STATUS IN THE DEVELOPMENT OF A STUDENT’S PERSONALITY - Haydarova, S.S (Educational Research in Universal Sciences, 2024)
In this article, opinions are expressed about the role of status in the formation of students as a person in interpersonal relationships, which plays an important role in its development.